2021
DOI: 10.1186/s12284-021-00533-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Elite Core Panel as a Key Breeding Resource to Accelerate the Rate of Genetic Improvement for Irrigated Rice

Abstract: Rice genetic improvement is a key component of achieving and maintaining food security in Asia and Africa in the face of growing populations and climate change. In this effort, the International Rice Research Institute (IRRI) continues to play a critical role in creating and disseminating rice varieties with higher productivity. Due to increasing demand for rice, especially in Africa, there is a strong need to accelerate the rate of genetic improvement for grain yield. In an effort to identify and characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…It is important to note that an elongation initiation factor (eIFG tsv1 ) has been identified as a candidate gene and allele specific SNPs have been identified for tsv1 36 . With the availability of 3 K genome sequence better haplotypes can be searched for tsv1 52 . Use of superior haplotypes and tightly linked gene specific markers can further improve the efficiency of MABB 53 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that an elongation initiation factor (eIFG tsv1 ) has been identified as a candidate gene and allele specific SNPs have been identified for tsv1 36 . With the availability of 3 K genome sequence better haplotypes can be searched for tsv1 52 . Use of superior haplotypes and tightly linked gene specific markers can further improve the efficiency of MABB 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Modern breeding strategies focus on rapid-cycle recurrent selection achieved through intercrossing the best elite lines identified in each breeding cycle. A drawback often highlighted in this approach is that it produces (indeed relies on) a breeding program that is effectively closed; it is difficult to introduce new genetic variation from external sources, as these typically do not have equivalent performance with current elite cohorts (Juma et al 2021). This becomes a problem when the breeding program lacks key variations for major QTLs, such as major disease resistance or abiotic stress tolerance genes (Cobb et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…A key limitation in the ability of breeding programs to leverage these benefits of major-gene markerassisted selection is the availability of those genes in appropriate elite germplasm (Bhatia et al 2016;Janaki Ramayya et al 2021). Studies on current breeding programs have shown that about half of the genes and QTLs that could be useful are not found in current elite material; a further 15% or so are present at very low levels (Cobb et al 2019b, a;Juma et al 2021). Furthermore, these genes are mostly only available from very poorlyperforming landraces or occasionally very old breeding material.…”
Section: Introductionmentioning
confidence: 99%
“…The use of genes and QTLs through marker-assisted selection could shorten the breeding process. Although hundreds of stress-tolerance genes, QTLs, and physiological mechanisms have been identified, only a small number of these research outputs have been used in breeding ( Wissuwa et al, 2016 ; Cobb et al, 2019 ; Platten et al, 2019 ) and the frequency of known abiotic stress QTLs in the current elite breeding material remains low ( Juma et al, 2021 ). There is thus a need to bridge the gap between upstream science and breeding for adaptation to climate change so that valuable traits/genes/QTLs are more actively utilized in breeding pipelines.…”
Section: Can We Develop Climate-resilient Crops?mentioning
confidence: 99%